Corpus Literacy Training for In-Service English Language Teachers - Ahmet Basal; Erdem Akbaş; Betül Bal-Gezegin (Universidad Nacional de Colombia, 2024)
Corpus analysis offers a more accurate understanding of a language than intuition but is not widely used in foreign language instruction. This study uses a hermeneutic-phenomenology approach and content analysis to examine the impact of a corpus literacy course on the perceptions and performance indicators of 29 English language teachers. The results suggest that corpus literacy instruction is crucial for language teachers to incorporate corpus into their classroom practices effectively. Even a brief, intensive corpus literacy course can positively alter teachers' perceptions and abilities, increase their awareness of corpus usage in language teaching, and equip them with the skills needed, highlighting the importance of incorporating corpus literacy into the design of English language teacher education programs.